ETIKA DAN PROFESIONALISME GURU DALAM MEMBENTUK KARAKTER RELIGIUS PESERTA DIDIK DI ERA KURIKULUM MERDEKA - Nur Fitriani, Indah; Ubaidilah, Firman; Munawir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Amidst the complex challenges of modern education, teacher ethics and professionalism emerge as two fundamental aspects that play a strategic role in shaping the moral and intellectual qualities of students. Teacher ethics and professionalism are two fundamental aspects in education that play a crucial role in shaping students' religious character. This study aims to provide an understanding of the role of teacher ethics and professionalism, and their relationship to religious character formation in educational settings. Teacher ethics encompass attitudes, values, and behaviors that reflect exemplary behavior. Professionalism, on the other hand, relates to teacher competence, responsibility, and the quality of teacher performance in the learning process. Through a literature review, it was found that good teacher ethics can serve as the primary foundation for instilling religious values in students through role models and daily interactions. Furthermore, teacher professionalism strengthens this process through systematic lesson planning, the use of effective methods, and the ability to create a conducive learning environment. The synergy between teacher ethics and professionalism results in a more optimal internalization of religious values, so that students not only understand religious teachings cognitively but are also able to implement them in their daily lives. Thus, teacher ethics and professionalism contribute significantly to shaping students' religious character and therefore need to be continuously developed as part of efforts to improve the quality of education.